Influence of Fertilizer Application Method on Phosphorus Availability to Maize Crop in Calcareous Soil - Sattar, Mehwish; Ikram, Wasiq (International Journal of Nanotechnology and Allied Sciences, 2023)
Low availability of phosphorus and high fixation in soils make it an essential component and a major limiting factor of plant growth. Recent developments in science favor the use of phosphorus fertilizers and animal manure on agricultural land to boost soil P fertility and crop productivity, but it has resulted in environmental damage in recent decades. This review will cover the influence of amended phosphate fertilizer on the availability of phosphorus to Maize in calcareous soil. Increased P uptake efficiency, reduced overuse of inorganic fertilizers P, and improved manure P recycling efficiency are just a few of the measures that can be used to achieve total P management in order to obtain high P use efficiency and Maize productivity.